2019
DOI: 10.1159/000500667
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Vasopressin V2 Receptor Antagonist on Polycystic Kidney Disease Development in a Rat Model

Abstract: Background: Vasopressin V2 receptor inhibition is a clinically validated mechanism of action in the treatment of autosomal dominant polycystic kidney disease (ADPKD). In this study, the effect of lixivaptan, a potent, selective vasopressin V2 antagonist, was evaluated in PCK rats, a validated animal model of PKD. Methods: Four-week old PCK rats were fed rodent chow with 0.5% lixivaptan (low dose) or 1% lixivaptan (high dose), or chow only (control) for 8 weeks. Urine output was measured at weeks 7 and 10 of ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 14 publications
0
21
0
Order By: Relevance
“…On the other hand, kidney weight/body weight and microalbuminuria indicated the severity of kidney disease. 17,18 In our study, kidney weight/body weight and microalbuminuria of mice analysis indicated that the kidney weight/body weight and microalbuminuria in HFDinduced mice were significantly increased compared with control group, which was markedly reduced by valsartan or silibinin ( Figure 5B and C). Moreover, combination treatment exhibited better anti-fibrosis effect compared with valsartan or silibinin ( Figure 5B and C).…”
Section: Silibinin In Combination With Valsartan Exhibited Significanmentioning
confidence: 48%
“…On the other hand, kidney weight/body weight and microalbuminuria indicated the severity of kidney disease. 17,18 In our study, kidney weight/body weight and microalbuminuria of mice analysis indicated that the kidney weight/body weight and microalbuminuria in HFDinduced mice were significantly increased compared with control group, which was markedly reduced by valsartan or silibinin ( Figure 5B and C). Moreover, combination treatment exhibited better anti-fibrosis effect compared with valsartan or silibinin ( Figure 5B and C).…”
Section: Silibinin In Combination With Valsartan Exhibited Significanmentioning
confidence: 48%
“… 51 Regarding the role of metformin, the outcomes of the TAME-PKD trial 52 are awaited to shed light on its efficacy and the frequency of its adverse effects, especially gastrointestinal ones. Interestingly, lixivaptan has been shown to effectively reduce kidney volume in a rat model of the disease, 53 while a toxicology modeling study has suggested its beneficial safety profile; 54 however, its clinical utility remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Tolvaptan slows ADPKD progression by blocking vasopressin-stimulated pathways, lowering intracellular cAMP, and inhibiting fluid secretion. In rodent models, treatment with vasopressin aggravated the development of ADPKD, while antagonism of its receptor helped preserve renal function ( Hopp et al, 2015 ; Wang et al, 2019a ). Blocking the V2R with tolvaptan can affect the extracellular signal-regulated kinase (ERK) pathway, cAMP production, and Cl − secretion ( Reif et al, 2011 ; Aihara et al, 2014 ; Kanhai et al, 2020 ).…”
Section: Available Adpkd Treatment and The Mechanisms Behind Itmentioning
confidence: 99%